2005
DOI: 10.1103/physrevlett.95.197203
|View full text |Cite
|
Sign up to set email alerts
|

Scaling and Renormalization Group in Replica-Symmetry-Breaking Space: Evidence for a Simple Analytical Solution of the Sherrington-Kirkpatrick Model at Zero Temperature

Abstract: Using numerical self-consistent solutions of a sequence of finite replica symmetry breakings (RSB) and Wilson's renormalization group but with the number of RSB steps playing a role of decimation scales, we report evidence for a nontrivial T-->0 limit of the Parisi order function q(x) for the Sherrington-Kirkpatrick spin glass. Supported by scaling in RSB space, the fixed point order function is conjectured to be q*(a)=sqrt[pi]/2 a/xi erf(xi/a) on 0 a at T =0 and xi approximatel… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
50
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 32 publications
(52 citation statements)
references
References 18 publications
2
50
0
Order By: Relevance
“…Recently Oppermann and coworkers [24] have investigated the replica symmetry breaking solution for T = 0 in high order. They find = −0.763 · · · and again a linear behavior of the local field distribution with slope 0.3.…”
Section: Multi Step Replica Symmetry Breakingmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently Oppermann and coworkers [24] have investigated the replica symmetry breaking solution for T = 0 in high order. They find = −0.763 · · · and again a linear behavior of the local field distribution with slope 0.3.…”
Section: Multi Step Replica Symmetry Breakingmentioning
confidence: 99%
“…The local field distribution obtained from the Edwards measure [16,19,20] is discussed in Section 3 and Appendix A. The local field distribution has also been computed in high orders of replica symmetry breaking by Oppermann et.al [24]. This is discussed for comparison in Section 4.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Through accurate studies of a large sequence of finite-replica-symmetry breakings Refs. [9] and [10] have demonstrated that within replica theory the correct linear behaviour of P (h) for the SK model requires the full limit of infinite replicasymmetry breaking order; any finite-order truncation yielding a fictitious (if decreasing with RSB-order) hole in P (h) near h = 0.…”
Section: Local Field Distributionsmentioning
confidence: 99%
“…Since then there have been several further studies of P (h) for the SK model (see, for example, Refs. [7], [8], [9], and [10]) and the nature of the local field distributions is well understood. On the other hand, there has been little work on the study of P (h) for other spin-glass models.…”
Section: Introductionmentioning
confidence: 99%